INTERNATIONAL LEGAL AND INSTITUTIONAL BASIS OF ANTITERTERRORIST POLITIC - Целуйко, М.Є. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2015)
This article exposes activity of basic international antiterterrorist institutes at two levels: global and regional. The last is presented with western and east regions. The structure of organizations, groups, experience and work assignments, existent problems are discussed in this article. Antiterterrorist legislative acts, lyings in basis of activity of international institutes, are considered.